Consumer perceptions and preferences of pharmacist-led professional services and attributes in Australia: a qualitative focus group study - Ruth Webster; Suzanne Robinson; Richard Norman; Laura Thomas; Ajay Karia; Tin Fei Sim (BMJ Open)
Objective This study investigates consumer views of pharmacist-led professional services in Australia, emphasising factors influencing their uptake and attributes valued by users.Design Semi-structured online focus groups explored the awareness, experiences and expectations of pharmacists and pharmacy professional services. Audio recordings were transcribed verbatim and de-identified. Data were analysed using the thematic analysis technique to identify common themes.Setting Three online focus groups were conducted, inviting participants from AustraliaParticipants 15 adults aged 18 years and above, English-speaking and self-identified as a consumer of health services or a health carer.Results Participants recognised pharmacists primarily as medication experts but also valued additional services like health screening, vaccination and chronic disease management. Consumer perceptions and experiences of professional pharmacy services focused on three themes: (1) convenience, (2) credibility and trust, and (3) communication and awareness. More specifically, attributes that influence service uptake include pharmacist competency, general practitioner (GP) endorsement, service availability, convenience, awareness and cost. Competency was associated with visible qualifications and specialised training, fostering consumer trust. Limited awareness of available services and privacy concerns posed barriers. Collaborative relationships between pharmacists and GPs, flexible hours and minimal waiting times, provision of services within pharmacists’ scope of practice and recognition from the government were particularly appealing factors.Conclusions The findings highlight opportunities to expand pharmacists’ roles in primary care, emphasising the need for tailored attributes, robust competency frameworks, GP endorsement and government support for sustainable service models. This work contributes to the growing evidence base on enhancing consumer-centred pharmacy services, guiding policy and practice improvements to meet evolving healthcare demands. Future research quantifying how much consumers value each attribute can help providers with limited resources prioritise better.